Diseño e implementación de luces LED inteligentes para los faros del automóvil Chevrolet AVEO - Ortiz Betancourt, Guillermo Arturo (2018)
The LED light is changing the way to get better lighting at night with high energy Efficiency index, following this concept we used a LED matrix with magnifiers or light concentrators coupled in the headlights of a Chevrolet AVEO, with this configuration It can generate greater light concentration by improving the visual acuity for the driver. This project will allow to avoid the glare in the drivers that are in the opposite direction to this system of headlights Smart, an automated system that uses the artificial vision by means of a camera as the main tool, that allows to detect the light of the other vehicle and to position it in such a way that by programming on the ARDUINO card it gradually reduces the Light intensity. In addition, by means of surveys, an acceptance of the system was obtained with a 83.88% in favor and a 16.12% against by several factors, such as the cost of implementation or the amount of light emitted by the Lighthouses among others, thanks to this data it was possible to analyze that the design has a great reception for providing better lighting in the roadway for the driver at night avoiding the glare or eye glare, without breaking the laws or norms already Established by the National Transit Agency (ANT).